Kontribusi Modal Sosial dalam Penerapan Manajemen Pengetahuan Usaha Kecil dan Menengah Kluster Kerajinan di Bogor - Anggraini Sukmawati; Lindawati Kartika (Institut Pertanian Bogor, 2014)
Activities of tourist visit provide opportunities for small and medium enterprises (SMEs) to stand, making the city of Bogor as one of the city that has an increasing number of SME’s. Failure to exploit the potential of the center to develop its organization and social capital owned SME’s indicate that SME’s still face problems of low quality human resources. SME’s mostly poorly educated human resources with technical expertise, competence, entrepreneurship and management are modest. On the other hand the knowledge inherent in members of an organization need to be updated and transferred to still have a value that is integrated with the vision and mission of the organization. On the basis of need, there is a knowledge management approach known as knowledge management.This study aims to (1) analyze the characteristics of social capital owned SME’s organizations Bogor, (2) analyze the characteristics of knowledge management in Bogor SME’s organization, (3) analyze the contribution and role of social capital on organizational knowledge management implementation, (4) analyze the relationship between social capital variables with the variables of organizational knowledge management practices of SME’s Bogor. This study used structural equation modeling (SEM) analysis.